Er-YAG LASER AND DENTAL CARIES TREATMENT OF PERMANENT TEETH IN CHILDHOOD. - Galia G. Zhegova; Maya R. Rashkova (Peytchinski Publishing, 2015)
The aim of this study was elaboration, approbation in a clinical situation and monitoring of the optimized protocol for application of Er:YAG laser "Lite Touch" in dental caries treatment of permanent teeth in children. Materials and methods: Fifty children between the age of 6 and 16 years with at least one bilateral matched pair of one type cavitated carious lesions in permanent teeth were included in the study. In each patient one of the 2 cavities was prepared conventionally, the other with the Er:YAG laser. All cavities were restored with light-cured composite resin following the application of acid etch and a bonding agent. Postoperative hypersensitivity, secondary caries and marginal morphology of restoration were evaluated. Results: No postoperative sensitivity and secondary caries in all children at the 2-year follow-up examination were observed. It was found that 94.83 % of restorations in Er:YAG laser treated carious lesions were clinically acceptable and no one of the restorations was lost. Conclusion: There is no difference with regard to the clinical success between laser and conventional treatment. The protocol with Er:YAG laser "Lite Touch" parameters used can be recommended in the dental practice for caries treatment of permanent teeth in childhood.